LEGAL FRAMEWORKS INFLUENCE ON BIOSOCIAL PROJECTS IN INFORMAL SETTLEMENT IN NAIROBI COUNTY ,KENYA - Njeri, Ngacha; Gakuu, Prof.Christopher; Kidombo, Prof.Harriet (Advances in Social Sciences Research Journal, 2020)
This study sought to establish Legal frameworks influence on performance of biosocial projects in informal settlements in Nairobi County, Kenya. The objective of this study was to establish the extent to which legal frameworks influence performance of biosocial projects in informal settlements. The variable indicators were: Existence of international legislations, compliance of national legislations, enforcement of County legislations and lastly inclusivity of Non-state actor’s policies. The study was premised on classical communication theory and theory of constraint. This study adopted pragmatism and mixed research approach to examine the legal frameworks influence on performance of biosocial projects while descriptive and correlational research designs were adopted. Quantitative data was collected through structured self-administered questionnaires while qualitative data was collected through interview guides after the research instruments were pilot tested for validity through content related method and reliability through test-retest criterion. A sample size of 183 individuals from 61 biosocial projects were selected from a target sample of 70 biosocial projects in Nairobi County through Gakuu, Kidombo and Keiyoro, 2016 sampling formula (s= (z/e)2). Quantitative data was computed from structured questionnaires administered to 61 staff members working in the selected biosocial projects and 61 beneficiaries of the biosocial projects besides qualitative in- depth interviews with 61 State and non-state actors through purposive sampling technique. The statistical tools of analysis that were used for descriptive data were the arithmetic mean and the standard deviation while the statistical tools of analysis that were used for inferential statistics were Pearson’s Product Moment Correlation (r) and Stepwise Regression (R2). F-tests were used to test hypotheses in the study. Tests of statistical assumptions were carried out before data analysis to avoid invalidation of statistical analysis. From the data analysis the null hypothesis that stated there is no significance relationship between legal frameworks and performance of biosocial projects in informal settlements in Nairobi County was rejected with r = 0.382, F = 15.207 at p = 0.000<0.01 and concluded that there is moderate relationship between Legal frameworks and performance of biosocial projects in informal settlements. In conclusion, there were noted key legislations supporting biosocial projects and biosocial community among them being constitution of Kenya 2010 that prohibits discrimination, The Persons with Disabilities Act, 2003, the act being an all-inclusive law encompassing rehabilitation rights and equal opportunities for people with disabilities. It creates the National Council of Persons with Disabilities as a statutory organ to oversee the welfare of persons with disabilities. The Law also obliges that both public and private sector employer’s reserve five percent of jobs for disabled persons. Conversely, there is correspondingly the National Security Act, chapter 258, Laws of Kenya, the law alludes to the benefit for worker incapacitated before the established retirement age and National Social Security Fund Act, 1965 (sessional paper number 5 of 1997), amended in 2001, the subject contains a provision which states that mental and physical disabilities shall not be considered as leading to work incapacity.